¿La incertidumbre importa? El crecimiento económico y el crimen: un análisis para América Latina y el Caribe en el periodo del 2008-2017 - Apaza Canchari, Yelsin Boris (2022)
This study seeks to analyze and measure the effect of crime and uncertainty1 on economic growth for 19 countries in Latin America and the Caribbean during the period 2008-2017. Based on the dynamic data panel methodology, it is found that uncertainty increases the adverse effect of crime on economic growth per capita, consequently crime can reduce annual GDP growth by 0.6% Likewise, the degree of compliance and rights of property increase GDP growth by 7%, moreover, it is confirmed that in the Latin American region the greatest explanatory value of economic growth is found in human capital.